Cruciform and circular church a comparative study on form and function during low mass celebrations - Marquez, Jennifer Marie M.
This study sought to find out the differences between a circular form and a cruciform church in terms of promoting an environment conducive to the spiritual growth of the assembly during low mass celebrations. The comparative research design using a multi-method approach was the major method used in this study. Both qualitative and quantitative data were generated through the use of observation schedules, behavioral maps and questionnaires. These methods helped identify the differences that existed between a cruciform and circular formed church based on the behavior and response of the assembly using physical, environmental and proxemic design considerations. Among the several methods of Observation, three were deemed useful in conducting this study. These were Direct Observation Method, Participant Observation, and Systematic Observation. Results and findings showed that in comparing the UP Chapel and the San Agustin Church, the prevailing characteristic in both church forms lies primarily on the arrangement of furniture. This was the most influential factor in comparing which form provided a more suitable environment for the assembly because this dominating characteristic produced significant differences regarding ventilation, restricted space utilization during the celebration of the mass, social behavior and iconographic function in the two forms. It was concluded that the ultimate reason why the church forms involved in this study produced varying experiential accounts from each other was a result of the physical environment. In this study, it was inferred that a circular church or the UP Chapel provided a better environment for the mass goers because the form of the chapel was more sensitive to the basic needs and comfort of its users and it fostered an environment where active and conscious participation was strongly emphasized.